(untitled) (Journal of Pharmaceutical Negative Results, 2022)
An injury to the skin or other organic tissue, known as a burn, is primarily brought on by heat, radiation, radioactivity, electricity, friction, or contact with chemicals. Burns also include skin wounds brought on by UV rays, radioactivity, electricity, or chemicals, as well as lung damage brought on by smoke inhalation. Burns are a significant public health issue on a global scale. According to estimates, there are 265 000 deaths annually from flames alone, with additional deaths from scalds, electrical burns, and other types of burns for which there are no published global statistics. In low- and middle-income nations, burns caused by fire account for almost 96% of all fatalities. Millions more people are left with lifelong disabilities and disfigurements in addition to those who pass away, frequently leading to rejection and stigma. Burns are incredibly preventable, making the misery they cause sadder.1 Through effective preventative measures and advancements in the care of burn victims, high-income countries have achieved significant progress in reducing the rate of burn deaths.